Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/7595374
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-128-3p Attenuated Doxorubicin-Triggered Acute Cardiac Injury in Mice by the Regulation of PPAR-γ

Abstract: Background. The clinical usefulness of doxorubicin (DOX), an anthracycline with antitumor activity, is limited by its cardiotoxicity. Oxidative stress and myocardial apoptosis were closely associated with DOX-induced cardiac dysfunction. It has been reported that microRNA-128-3p (miR-128-3p) was involved into the regulation of redox balance. However, the role of miR-128-3p in DOX-related cardiac injury remains not yet understood. The aim of this study was to investigate the biological effect of miR-128-3p in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
0
8
1
Order By: Relevance
“…Little doxorubicin-induced apoptotic effect in acute DIC model was reported by other groups (41)(42)(43)(44). However, it was also reported that DOX caused a great amount of apoptotic cardiomyocyte in an acute DIC model (45)(46)(47). Maybe apoptosis plays less important role in cardiac atrophy of acute DIC than we thought.…”
Section: Introductioncontrasting
confidence: 47%
“…Little doxorubicin-induced apoptotic effect in acute DIC model was reported by other groups (41)(42)(43)(44). However, it was also reported that DOX caused a great amount of apoptotic cardiomyocyte in an acute DIC model (45)(46)(47). Maybe apoptosis plays less important role in cardiac atrophy of acute DIC than we thought.…”
Section: Introductioncontrasting
confidence: 47%
“…To inhibit AMPK α , mice were intraperitoneally with CpC (20 mg/kg) once two days for 3 times before miR-1224-5p antagomir treatment [ 4 ]. To inhibit PPAR- γ , mice were pretreated with GW9662 (0.35 mg/kg/day in drinking water) for 10 consecutive days as previously described [ 27 , 28 ]. The animal protocols were approved by the Animal Experimentation Ethics Committee of Zhongnan Hospital of Wuhan University and were also in accordance with the guidelines of the National Institutes of Health for live animals.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the role of miR-1224-5p in vitro , cells were pretreated with the miR-1224-5p agomir (50 nmol/L), antagomir (50 nmol/L), or corresponding controls using Lipo6000™ Transfection Reagent for 24 h, cultured in fresh medium for an additional 24 h, and then stimulated with or without LPS (100 ng/mL) for 6 h [ 4 , 19 ]. To inhibit AMPK α or PPAR- γ , cells were preincubated with CpC (20 μ mol/L) or GW9662 (10 μ mol/L) for 12 h before miR-1224-5p antagomir treatment [ 4 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Upon binding, the complex associates with the miR-128 promoter region, increasing miR-128 expression (Li et al, 2015). An increased miR-128 level was reported in DOX-treated hearts (Zhang et al, 2021b). miR-128 promotes apoptosis by inhibiting SIRT1, resulting in increased p53 acetylation and activity (Adlakha and Saini, 2013;Li et al, 2015).…”
Section: Mirnas Involved In P53 Regulationmentioning
confidence: 99%